High-Risk Localized and Locally Advanced Prostate Cancer - Izumi, Kouji (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Around 20%-30% of nonmetastatic prostate cancer patients have high-risk localized disease. The best treatment for high-risk localized disease is still unclear, and the reliability of the definition of "high-risk" may need to be validated first. Although recent advances in radiotherapy for prostate cancer have yielded excellent long-term results, even in high-risk localized disease, there are no studies directly comparing it with local treatment options, such as prostatectomy. To address current challenges in high-risk localized and locally advanced prostate cancer, 12 original and 3 review articles covering aspects from basic research to clinical trials are published in this Special Issue.